2020
DOI: 10.3390/en13225893
|View full text |Cite
|
Sign up to set email alerts
|

Roadblocks to Low Temperature District Heating

Abstract: Energy usage in buildings is coming increasingly under the spotlight as carbon policy focus shifts towards the utilization of thermal energy. In the UK, heating and hot water accounts for around 40% of energy consumption and 20% of greenhouse gas emissions. Heating is typically produced onsite, making widescale carbon or energetic improvements challenging. District heating networks (DHNs) can offer significant carbon reduction for many users but can only be implemented if the end user buildings have good therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…As evidenced, the total amount of networks considered to be carbon neutral is only about 31%, meaning that gas fired CHP is the largest contributor to networks being not considered as carbon neutral. The high implementation of gas fired CHP could be due to a number of reasons, one being the relief to the electrical infrastructure it provides, which is discussed by Millar et al [53] as being a critical challenge as electrification of heat is becoming more popular. Another reason could be due to the cost effectiveness, as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced, the total amount of networks considered to be carbon neutral is only about 31%, meaning that gas fired CHP is the largest contributor to networks being not considered as carbon neutral. The high implementation of gas fired CHP could be due to a number of reasons, one being the relief to the electrical infrastructure it provides, which is discussed by Millar et al [53] as being a critical challenge as electrification of heat is becoming more popular. Another reason could be due to the cost effectiveness, as seen in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a substantial variation in what current temperatures are in existing networks compared to what they are proposed to be in a future 5G networks. Millar et al [53] report that it is generally accepted that 5G ambient networks is in the region of 10-40 • C. However, Averfalk and Werner [54] argues that the existing documentation of low temperature systems displays no average system return temperature below 30 • C. This suggests that existing low temperature networks in operation are not designed to temperatures as low as stated by Millar et al [53] or that the heat source is not operating reciprocally to the dynamic heat loads within the network. There are many articles supporting the idea of low temperature distributions, such as Lund et al [26], who acknowledged that lower temperatures, combined with small pipes, reduce distribution heat losses to existing networks by roughly 75%.…”
Section: Design Temperaturesmentioning
confidence: 99%
“…Presented in the paper algorithm could be implemented in DHS performance monitoring systems to increase the accuracy of water loss measurement. This is particularly important for modern fourth-and fifth-generation district heating systems [4,40,41], where low heat transport losses are mandated [42,43]. Figure 11 refers to a DHS that is not equipped with an excess water storage tank or thermal energy storage.…”
Section: Discussionmentioning
confidence: 99%
“…The friction factor is calculated by the Darcy-Welsbach Equation [92] and is used for calculating the friction loss in a pipe, the value is calculated by two methods dependent on the flow regime. Laminar flow is described by Equation ( 42): μ = 64Re −1 (42)…”
Section: Data Availabilitymentioning
confidence: 99%